A PETAR method for risk assessment of human health and environment on the regional scale. (21st May 2022) - Guo, Kai; Liu, Yang; Lan, Zeying; Qin, Liangjun; Lin, Tong; Gan, Qiao; Jin, Bingbing; Chen, Min
Abstract: Risk assessments are necessary to effectively reveal the state of the degradation of living environments on a regional scale. However, risk assessments are often limited by time, cost, and technology, which make conducting effective evaluations difficult. Thus, in this study, the procedure for ecological tiered assessment of risk (PETAR) method was used to analyze the human health and environmental risks in Daye, China. This method first used the United States Environmental Protection Agency's risk assessment approach to qualitatively determine the risk sources, pressures, receptors, and effect endpoints and constructed a conceptual model of threats to the human living environment. Each risk‐prone subregion was then evaluated using the fuzzy logic method. Next, a quantitative assessment was conducted for the subregions with the most serious environmental degradation. Finally, quantitative analyses were performed to verify the original hypotheses. The results showed that the high‐risk areas were distributed in the industrial regions of Daye, wherein mining and processing clusters and mining settlements are widespread and confirmed the locations of the particular subregions with the most serious human health and environmental risks. This study also validated the practicality of the PETAR method for human health risk assessments in mining areas with large‐scale, multifactor, and multihazard paths. Integr Environ Assess Manag 2023;19:239–253. © 2022 SETAC KEY POINTS: Overall, the resultant environmental and health risks in the 17 studied towns were found to be reasonable. Quantitative analysis of particular subregions validated earlier ecological hypotheses, producing important information for real‐world assessments. The PETAR method combines qualitative and quantitative procedures, making it more convenient to identify health hazards on a large scale. The PETAR method makes cumbersome risk‐test procedures obsolete.